The Impact of Ethical Practices on the Performance of Small and Medium Enterprises in South Africa - Dzomonda, Obey; Fatoki, Olawale (Journal of Economics and Behavioral Studies, 2017)
SMEs have become beacons of hope towards improving economic growth and development of many countries globally. However, the literature documents a high discontinuance rate among small businesses. The purpose of this study is to investigate the impact of ethical practices on the performance of SMEs in South Africa. The study was based on a quantitative research design. The survey method was used as a data collection method. Using this method, self-administered questionnaires were used as the primary data collection tool. These questionnaires were hand delivered to the participants by the researcher. The random sampling method was used to obtain the participants. The population consisted of SME owner/managers in Polokwane municipality. 74 SME owner/managers participated in the survey. Data analysis included descriptive statistics, factor analysis, T tests and regression analysis. The Cronbach’s alpha was used as a measure of reliability. The findings showed that SMEs display unethical behavior and a weak performance. It was discovered that SMEs does not have policies in place to guide their ethical behavior. The T test results showed significant differences between gender and education levels with ethical practices of SMEs. The regression results showed that there is a positive relationship between ethical practices and performance of SMEs. Recommendations were made for SMEs to treat ethical issues seriously lest they risk incurring costs associated with lawsuits and negative brand reputation.